Assessment of the cutaneous immune response during Arthroderma benhamiae and A. vanbreuseghemii infection using an experimental mouse model. (1st March 2014) - Cambier, L.; Weatherspoon, A.; Defaweux, V.; Bagut, E.T.; Heinen, M.P.; Antoine, N.; Mignon, B.
Summary: Background: Dermatophytoses are common but poorly understood skin infections. Most in vivo studies have been performed using the guinea pig as the experimental animal model, which has several limitations. Objectives: To develop a mouse model of dermatophytosis suitable for multiple purposes, including the investigation of immunity against dermatophytes. Materials and methods: Two peculiar fungal species, Arthroderma benhamiae and A. vanbreuseghemii, isolated from tinea in humans having contact with rodents were used for epicutaneous inoculation. During the infection, clinical and histopathological follow‐up were performed. The recruitment of immune cells was evaluated by immunofluorescence staining and the levels of cytokine mRNA were quantified by quantitative reverse transcriptase‐polymerase chain reaction in the skin of infected mice. Results: The skin symptoms and microscopic lesions, including the colonization of keratinized epidermal and follicular structures by both dermatophytes, were highly similar to those observed in guinea pig infection models and in natural infections, mimicking acute superficial tinea in humans. The dermal inflammatory cellular infiltrate consisted of macrophages, dendritic cells and especially polymorphonuclear neutrophils, which are one of the histological 'clues' to the diagnosis of dermatophytosis. The in situ cytokine profile was characterized by the overexpression of transforming growth factor‐β, interleukin (IL)‐1β and IL‐6 mRNA during infection, suggesting a role of the T‐helper 17 pathway in the establishment of immunity. Conclusions: Our new reproducible and validated mouse model of dermatophytosis is a modern in vivo tool that allows a more in‐depth understanding of the pathogenesis of human dermatophyte infections.